Prospective memory impairment and its implications for community living skills in bipolar disorder. (6th September 2013) - Au, Raymond WC; Ungvari, Gabor S; Lee, Edwin; Man, David; Shum, David HK; Xiang, Yu‐Tao; Tang, Wai‐Kwong
<x xml:space="preserve">Abstract</x> Objective Prospective memory (PM) refers to the ability to undertake intended actions in the future. The functional significance of PM in bipolar disorder (BD) has not yet been investigated. This study examined PM impairment and its role in community living skills in clinically stable individuals with BD. Methods Seventy‐six individuals with BD and 44 healthy individuals were assessed with the Chinese version of the Cambridge Prospective Memory Test. Socio‐demographic characteristics, retrospective memory (RM; the ability to recall or recognize past information), and intelligence were also measured in all participants. The clinical condition and community living skills of patients with BD were rated independently with standardized instruments. Results Patients with BD showed PM impairment and their PM total scores independently predicted the level of community living skills in regression analyses. In follow‐up analyses, the contribution was found to be accounted for by the time‐based PM scores. Conclusions Given the expanding body of research on the utility of PM in predicting functioning, these findings further support the role of PM in community living skills in individuals with BD. The results suggest that PM training might be an integral part of clinical rehabilitation devised for individuals with BD.